The Shadow Side of Migration—Relation Between Crime and Illegal Immigration in the Nordic Countries. - Butt, Junaid Sattar (Acta Universitatis Danubius. Relationes Internationales, 2024)
Illegal immigration is a contentious topic, particularly when linked to concerns about crime and presents multifaceted challenges to host countries, including the Nordic nations. In the complex landscape of international relations, the interplay between migration and crime has emerged as a pressing issue, particularly in the context of illegal immigration. The Nordic countries, known for their progressive social policies and focus on integration, are not immune to these discussions. While renowned for their social welfare systems and openness to immigration, these nations have also grappled with concerns about the impact of illegal immigration on public safety. Drawing upon interdisciplinary perspectives from criminology, international relations, and legal studies, the research explores the multifaceted dynamics of crime and migration, analyzing the socio-economic, political, and legal implications of irregular migration flows. This paper investigates the intricate nexus between crime and illegal immigration in the Nordic context. By examining empirical evidence and theoretical frameworks, the study sheds light on the various dimensions of this international relationship. It explores how illegal immigration intersects with criminal activities, including human trafficking, smuggling, and organized crime networks. Furthermore, the paper investigates the socio-economic factors that drive individuals to engage in illegal immigration and subsequent criminal behavior. Through a comprehensive analysis of existing literature and case studies, this research aims to provide insights into the complexities of the shadow side of migration in the Nordic countries. Understanding the dynamics of crime and illegal immigration is crucial for policymakers, law enforcement agencies, and civil society organizations to develop effective strategies for addressing these challenges while upholding human rights and promoting social cohesion.